2015
DOI: 10.15809/irriga.2015v1n1p107
|View full text |Cite
|
Sign up to set email alerts
|

Efeito Da Fertirrigação Com Potássio Sobre O Solo E Produtividade Do Morangueiro

Abstract: EFEITO DA FERTIRRIGAÇÃO COM POTÁSSIO SOBRE O SOLO E PRODUTIVIDADE DO MORANGUEIRO  EDILSON RAMOS GOMES1; FERNANDO BROETTO2; JOÃO GABRIEL THOMAZ QUELUZ3 E DAYANNE FABRÍCIO BRESSAN3 [1] Prof. Mestre, Departamento de Engenhara Rural, Universidade Estadual Paulista-UNESP, Faculdade de Ciências Agronômicas, Botucatu-SP. e-mail: edilsonevj@hotmai.com  2 Prof. Doutor, Instituto de Biociências, Universidade Estadual Paulista/UNESP, Departamento de Química e Bioquímica, Botucatu-SP.3 Doutorando (a) em Agronomia (Irrigaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…The increase in soil electrical conductivity was also observed by Gomes et al (2015), when applying potassium doses in strawberry cultivation, saline effect was observed on the soil and toxicity to plants at the highest dose of potassium applied. Anjos et al (2015) who also observed an increase in electrical conductivity from potassium fertilization, emphasized the saline effect of KCl applied via fertigation.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The increase in soil electrical conductivity was also observed by Gomes et al (2015), when applying potassium doses in strawberry cultivation, saline effect was observed on the soil and toxicity to plants at the highest dose of potassium applied. Anjos et al (2015) who also observed an increase in electrical conductivity from potassium fertilization, emphasized the saline effect of KCl applied via fertigation.…”
Section: Resultsmentioning
confidence: 76%
“…However, the traditional management of fertigation has led to excessive losses and applications, justifying the need for better control to guarantee both economic and environmental improvement (Anjos et al, 2015;Gomes et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Além de fatores naturais que provocam a salinização dos solos como o material de origem, o uso exagerado de fertilizantes químicos em conjunto com a irrigação aplicada de forma errônea também pode contribuir para o aumento dos níveis de salinidade. Nota-se que esses efeitos são mais acentuados sob condições de cultivo protegido, mesmas condições em que são produzidas a maioria das hortaliças no Brasil (GOMES et al, 2015).…”
Section: Introductionunclassified